Profile Picture on Social Networks: Effectiveness and Trends in How to Introduce Ourselves in the Virtual World - Mena, Sergio (VISUAL REVIEW. International Visual Culture Review / Revista Internacional de Cultura Visual, 2014)
To get transmit a loyal image of every social media profile is the reason why main social platform require insert a picture that identifies it. But every user is free to upload the picture they wish to and, thus, its heterogeneity is huge. However, there are some common point among them, like the background used, the gaze way or the space occupied by the face. Besides, there already are recommendations from human resources departments that guide of the effectiveness of those pictures when you want to give a good impression to others. This research aims to identify those common elements, count its appearances and determine what trends do exist between the common profile pictures through analyzing Facebook and Twitter profile matrixes.